1514 Higher Mortality in Pelvic Acetabular Fractures Is Associated with Lower Body Mass Index. (12th October 2021) - Waseem, S; Lenihan, J; Davies, B; Rawal, J; Hull, P; Carrothers, A; Chou, D
Abstract: Aim: Fractures of the pelvis and acetabulum can be life-threatening or life changing injuries. Multiple factors can contribute to outcome including age, frailty, and baseline nutritional status. The aim of this study was to identify if low BMI (<18.5) was a predictor of outcome for patients with such injuries in terms of morbidity and mortality. Method: We retrospectively analysed 1033 patients with pelvic or acetabular fractures referred to a single level 1 major trauma centre over a 4.5-year period (August 2015 - January 2020). Of these patients, 569 were admitted to the centre and included in our analysis. Data was collected on demographics, injury pattern, operative intervention, and complications. Comparison was made between patients that were underweight (BMI<18.5) and patients that were not, for in-hospital and post discharge complications including pulmonary embolus (PE), deep venous thrombosis (DVT), ileus, infection, loss of reduction and mortality at 6 months. Results: Underweight patients had a statistically significant increase in mortality both in-hospital (p = 0.019) and at 6 months post injury (p = 0.039) when compared to other BMI groups. No statistical significance was found between these BMI groups comparing morbidity: DVT (p = 0.712), PE (p = 0.736) nor ileus (p = 0.149). Covariate analysis showed that a low BMI was associated with 3 times increased in-hospital mortality after correction for age and energy of injury (adjusted OR 3.028, 95% CI 1.059-8.659). Conclusions: This study suggests increased mortality in patients with pelvic or acetabular fractures who are underweight. Surgeons should consider these findings in initiating appropriate peri-operative optimisation for these patients.